Executive power - Andrews, Brian, 1973-; Wilson, Jeffrey (Clancy, Tom, 1947-2013. Jack Ryan novel, 2025)
When Kyle Ryan--always the rebel in a family full of strong personalities--vanishes during an assignment in a politically unstable African nation, the stakes couldn't be higher. His warning to the Defense Intelligence Agency, "We're on the wrong side of history," suggests he uncovered something explosive. Now the country is sliding toward a coup, and Kyle's father, the President of the United States, faces an impossible choice: protect national interests or save his son. As political tensions escalate and loyalties are tested, the entire Ryan family is pulled into a crisis that could shatter them--and reshape global power.